Surface characterization of activated alumina powder through the mechano-chemical treatment for fabrication of non-fired ceramics - Takashi SHIRAI; Apiluck EIAD-UA; Tran Thi Thu HIEN; Masayoshi FUJI (My University, 2012)
Functional ceramics were synthesized using ceramic powders activated by mechanochemical processing. The activated powders were dispersed in an alkali-containing solvent to dissolve the metallic ions at the powder surface and effect re-precipitation between the grains. The "non-firing ceramic process" afforded high-strength ceramic solids without the need for calcination. The key step in this technique is surface activation of the ceramic powders through mechanochemical processing. We investigated the bonding and activity of the atoms near the surface by spectroscopic analysis of desorption of the adsorbed water molecules, a convenient and quantitative method. The powder surface contained an increased number of uncoordinated defects after mechanochemical processing, and powders with high compact strength showed high activity and had high surface AlV content. Diffuse reflectance infrared Fourier transform measurements of the desorption of water molecules allowed for easy and rapid determination of differences in the surface activity, which was not possible when using alternative analysis methods.
Keywords: Ferroelectric and Piezoelectric Materials